Teachers’ Attitudes Toward Inclusive Education in East Java, Indonesia - Junaidi, Ahsan Romadlon (Department of Special Education, 2020)
Teacher’s attitude towards inclusive education becomes an important variable for the successful implementation of the program. This research aims to examine whether there are differences of teachers’ attitude toward inclusive education in terms of the duration of training and the teaching experience of students with special needs. The research was conducted in regular schools that provide inclusive education services in East Java, at elementary, junior high school, high school and vocational high school. Data were collected using a questionnaire and analyzed with Two Path Variant Analysis. The results showed that there were significant differences of teachers’ attitude towards inclusive education. The more experienced and the longer the duration of the training, the more positive the teacher’s attitude towards inclusive education.